2008
DOI: 10.1177/1541204008320258
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Community, School, and Student Factors on School-Based Weapon Carrying

Abstract: Extant research has theorized that community conditions affect the level of student violence in and around schools, yet few studies have tested this proposition directly. This research does so by assessing whether social conditions in a school's attendance area affect the likelihood of students bringing weapons to school. Current results indicate that the level of economic disadvantage, residential mobility, and violent crime in a school's attendance area are unrelated to student-level weapon carrying. The imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 72 publications
2
34
1
1
Order By: Relevance
“…Furthermore, the fear and victimization hypothesis suggests protective weapon-carrying may be one of the adaptive responses to past victimization, and evidence regarding this outcome is also mixed. Both Wilcox, May, and Roberts (2006) and Watkins (2008) found that previous victimization was positively related to student weaponcarrying, though recent work by Cao, Zhang, and He (2008) found that neither past victimization nor fear of attack was significantly related to student weapon-carrying. Ultimately, the fear and victimization hypothesis has yet to be consistently supported across studies.…”
Section: Theoretical Framework and Previous Researchmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, the fear and victimization hypothesis suggests protective weapon-carrying may be one of the adaptive responses to past victimization, and evidence regarding this outcome is also mixed. Both Wilcox, May, and Roberts (2006) and Watkins (2008) found that previous victimization was positively related to student weaponcarrying, though recent work by Cao, Zhang, and He (2008) found that neither past victimization nor fear of attack was significantly related to student weapon-carrying. Ultimately, the fear and victimization hypothesis has yet to be consistently supported across studies.…”
Section: Theoretical Framework and Previous Researchmentioning
confidence: 97%
“…These recent studies suggest that measures of perceived disorder and victimization are simultaneously related to student fear (Melde & Esbensen 2009), student weapon-carrying (Watkins, 2008), and school avoidance behaviors (Randa & Wilcox, 2010). Furthermore, the latter-mentioned effects of disorder and victimization on school protective and avoidance behaviors were evident even after accounting for the potential mediating effects of fear (Randa & Wilcox, 2010;Watkins, 2008). In other words, both victimization and school disorder were important in understanding student adaptive behavior, but their effects were not fully explained by fear.…”
Section: Theoretical Framework and Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Pour Wilcox, May et Roberts (2006), ainsi que pour Watkins (2008), ni la victimisation antérieure ni la crainte d'être la cible d'attaques ne seraient significativement associées au fait d'apporter une arme à l'école. Webster, Gainer et Champion (1993) semblent plutôt indiquer que le port d'un pistolet chez les jeunes ferait partie d'un large ensemble de comportements agressifs liés à la délinquance et ne constituerait pas une stratégie pour se défendre contre la victimisation à l'école.…”
Section: Possession D'objets Potentiellement Dangereux à L'école Et Vunclassified